CB-MNCs@ CS/HEC/GP promote wound healing in aged murine pressure ulcer model - Zhi-cheng Yang; He Lin; Guo-jun Liu; Hui Pan; Jun-lu Zhu; Xiao-hong Zhang; Feng Gao; Zhong Wang; Zhi-hao Wang (Stem Cell Research & Therapy)
Abstract Background Non-healing pressure ulcers impose heavy burdens on patients and clinicians. Cord blood mononuclear cells (CB-MNCs) are a novel type of tissue repair seed cells. However, their clinical application is restricted by low retention and survival rates post-transplantation. This study aims to investigate the role of thermo-sensitive chitosan/hydroxyethyl cellulose/glycerophosphate (CS/HEC/GP) hydrogel encapsulated CB-MNCs in pressure ulcer wound healing. Methods Pressure ulcers were induced on the backs of aged mice. After construction and validation of the characterization of thermo-sensitive CS/HEC/GP hydrogel, CB-MNCs are encapsulated in the hydrogel, called CB-MNCs@CS/HEC/GP which was locally applied to the mouse wounds. Mouse skin tissues were harvested for histological and molecular biology analyses. Results CB-MNCs@CS/HEC/GP therapy accelerated pressure ulcer wound healing, attenuated inflammatory responses, promoted cell proliferation, angiogenesis, and collagen synthesis. Further investigation revealed that CB-MNCs@CS/HEC/GP exerted therapeutic effects by promoting changes in cell types, including fibroblasts, endothelial cells, keratinocytes, and smooth muscle cells. Conclusion CB-MNCs@CS/HEC/GP enhanced the delivery efficiency of CB-MNCs, preserved the cell viability, and contributed to pressure ulcer wound healing. Thus, CB-MNCs@CS/HEC/GP represents a novel therapeutic approach for skin regeneration of chronic wounds.